Genetic heterogeneity in ten families with myoclonus-dystonia. Issue 8 (16th July 2004) - Schüle, B; Kock, N; Svetel, M; Dragasevic, N; Hedrich, K; de Carvalho Aguiar, P; Liu, L; Kabakci, K; Garrels, J; Meyer, E-M; Berisavac, I; Schwinger, E; et al.
Abstract : Background: Myoclonus-dystonia (M-D) is a movement disorder with autosomal dominant inheritance and reduced penetrance but may also occur sporadically. Recently, mutations in the epsilon-sarcoglycan gene ( SGCE ) were shown to cause M-D. Furthermore, single variants in the dopamine D2 receptor ( DRD2 ) and DYT1 genes were found in combination with SGCE mutations in two M-D families, and another M-D locus was recently mapped to chromosome 18p11 in one family. Methods: The authors clinically and genetically characterised ten consecutive cases with myoclonus-dystonia; seven familial and three sporadic. Twenty nine M-D patients and 40 unaffected family members underwent a standardised clinical examination by a movement disorder specialist. Index cases were screened for mutations in the SGCE, DYT1, and DRD2 genes and for deletions of the SGCE gene. Suitable mutation negative families were tested for linkage to the SGCE region and to chromosome 18p11. Results: Two SGCE mutations were detected among the seven familial but no mutation in the sporadic cases. Haplotype analysis at the new M-D locus was compatible with linkage in two families and excluded in another family, suggesting at least one additional M-D gene. There were no obvious clinical differences between M-D families with and without detected mutations. Conclusion: M-D is genetically heterogeneous with SGCE mutations accounting for the disease in only part of the clinically typical cases.